Constitutively Active Arabidopsis MAP Kinase 3 Triggers Defense Responses Involving Salicylic Acid and SUMM2 Resistance Protein. Issue 2 (11th April 2017) - Genot, Baptiste; Lang, Julien; Berriri, Souha; Garmier, Marie; Gilard, Françoise; Pateyron, Stéphanie; Haustraete, Katrien; Van Der Straeten, Dominique; Hirt, Heribert; Colcombet, Jean
Abstract : The stress-activated MPK3 and the SUPPRESSOR OF MKK1 MKK2 1/2 module control a similar set of responses, which include accumulation of salicylic acid, reactive oxygen species, and phytoalexins and modulation of defense genes. Abstract: Mitogen-activated protein kinases (MAPKs) are important regulators of plant immunity. Most of the knowledge about the function of these pathways is derived from loss-of-function approaches. Using a gain-of-function approach, we investigated the responses controlled by a constitutively active (CA) MPK3 in Arabidopsis thaliana . CA-MPK3 plants are dwarfed and display a massive derepression of defense genes associated with spontaneous cell death as well as the accumulation of reactive oxygen species, phytoalexins, and the stress-related hormones ethylene and salicylic acid (SA ). Remarkably CA-MPK3 / sid2 and CA-MPK3 / ein2-50 lines, which are impaired in SA synthesis and ethylene signaling, respectively, retain most of the CA-MPK3 -associated phenotypes, indicating that the constitutive activity of MPK3 can bypass SA and ethylene signaling to activate defense responses. A comparative analysis of the molecular phenotypes of CA-MPK3 and mpk4 autoimmunity suggested convergence between the MPK3- and MPK4-guarding modules. In support of this model, CA-MPK3 crosses with summ1 and summ2, two known suppressors of mpk4, resulted in a partial reversion of the CA-MPK3 phenotypes. Overall, our data unravel a novel mechanism by which the MAPK signaling network contributes to a robust defense-response system.